Key aspects for evaluating user experience using eye tracking in immersive educational virtual reality environments - Martínez Moreno, Maria Fernanda; Gómez Acosta, Angie Carolina; Roa Martínez, Sandra Milena (Ingeniería Solidaria, 2026)
Introduction: The article is the result of the research “User Experience Evaluation in Educational Immersive Virtual Reality Environments with Eye Tracking,” conducted at the University of Cauca in 2025. Problem: Traditional methods fail to capture visual attention and cognitive load in real time, making it difficult to compare results. Objective: To identify and map approaches, trends, and eye-tracking metrics in UX evaluation for immersive VR educational environments, in order to pinpoint gaps and opportunities for more consistent, user-centered evaluation models. Methodology: Systematic review using the SALSA framework (protocol, application, and analysis), with scope defined by PICOC, focusing on population, intervention, outcomes, and the immersive educational context. Results: Metrics such as fixations, gaze trajectory, saccades, and pupilometry are highlighted, combined with subjective instruments. Challenges include small sample sizes, calibration issues, and symptoms of fatigue and cybersickness. Conclusion: A standardized methodological framework is needed, combining eye-tracking metrics with subjective perceptions. While eye tracking is increasingly being adopted, gaps remain in sample sizes, cybersickness control, and experience duration. Originality: Provides an updated synthesis of the intersection between immersive VR educational environments and eye tracking, with a mapping of technologies, metrics, and methods, and highlights gaps to improve future frameworks and studies. Limitations: Variability in configurations and protocols, small sample sizes, calibration issues, visual fatigue, cybersickness, and conflicts between experimental control and naturalness.
Keywords: user experience; Virtual Reality; eye tracking; evaluation; systematic review